Land Snails from Northern Missouri - Richard L. Reeder; Charles D. Miles (Hello World!, 1976)
The state of Missouri has a rich land snail fauna. However, the knowledge of those species comprising the fauna and the details of their distribution are far from adequate. As pointed out by Miles (1969) and, more recently, Hubricht (1972a), the details of the northern fauna are particularly scanty. Locality records from north of the Missouri River are scattered in the literature, most reports having concerned the southern half of the state. A partial review of the literature devoted to Missouri land snails is included here.